TEACHING READING COMPREHENSION THROUGH LISTEN-READ-DISCUSS (LRD) STRATEGY TO THE ELEVENTH GRADE STUDENTS OF MAN 2 LUBUKLINGGAU - Popy Dwijayanti; Ardayati; Hamdan (Teaching and General Education Studies, 2026)
This research investigates the effectiveness of the Listen-Read-Discuss (LRD) strategy in improving reading comprehension of argumentative texts among eleventh-grade students at MAN 2 Lubuklinggau. Addressing challenges such as limited learning strategies, the study employed a pre-experimental design involving 40 students selected via purposive sampling. Data were collected using a 20-item multiple-choice test. The findings revealed a significant improvement in student performance, with average scores rising from 67.0 in the pre-test to 76.6 in the post-test. Statistical analysis yielded a t-obtained value of 10.02, substantially exceeding the t-table value of 1.685. Consequently, the null hypothesis was rejected, confirming that the LRD strategy is a significantly effective instructional tool. By fostering engagement and structured discussion, the LRD strategy enhances students' ability to decode complex argumentative texts. The researcher recommends that educators adopt this strategy across various contexts and suggests further studies to explore its long-term impact on diverse reading materials and student engagement levels.